Branching Morphogenesis - Davies, Jamie; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Branching morphogenesis, the creation of branched structures in the body, is a key feature of animal and plant development. This book brings together, for the first time, expert researchers working on a variety of branching systems to present a state-of-the-art view of the mechanisms that control branching morphogenesis. Systems considered range from single cells, to blood vessel and drainage duct systems to entire body plans, and approaches range from observation through experiment to detailed biophysical modelling. The result is an integrated overview of branching.
Why a Book on Branching, and Why Now? -- Branching Morphogenesis in Vertebrate Neurons -- Branching of Single Cells in Arabidopsis -- Branching in Fungal Hyphae and Fungal Tissues -- Branching in Colonial Hydroids -- How Is the Branching of Animal Blood Vessels Implemented? -- Extracellular Matrix Remodeling in Mammary Gland Branching Morphogenesis and Breast Cancer -- Branching Morphogenesis in Mammalian Kidneys -- Embryonic Salivary Gland Branching Morphogenesis -- Branching Morphogenesis of the Prostate -- Uterine Glands -- Physical Mechanisms of Branching Morphogenesis in Animals -- Afterword.
Keywords: Cell biology; Developmental biology; Life sciences; Plant physiology; Animal physiology; Cell Biology; Developmental Biology; Life Sciences, general; Plant Physiology; Animal Physiology